Towards the dictionary of the Russian women writers (from “the bibliographic catalogue” by Stepan Russov to the dictionary by Nikolay Golitsyn) - Dąbrowska, Magdalena (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The article contains a comparison of the three oldest dictionaries of the Russian women writers: 1. The bibliographical catalogue of the Russian women writers (1826) by Stepan Russov, 2. The materials to the history of the Russian women writers (1830, 1833) by Mikhail Makarov, 3. The bibliographical dictionary of the Russian women writers (1889) by Nikolay Golitsyn. There are presented also the works of Nikolay Bilevitch: The Russian women writers in 18th century and The Russian women writers in 19th century (1847), and Our women writers (1891) by Sergey Ponomaryov. The article treats on the history of the dictionaries and their structure (biographical and bibliographical materials).